2019
DOI: 10.1186/s12889-019-7441-6
|View full text |Cite
|
Sign up to set email alerts
|

Availability and readiness of diabetes health facilities to manage tuberculosis in Tanzania: a path towards integrating tuberculosis-diabetes services in a high burden setting?

Abstract: Background The burden of tuberculosis (TB) and diabetes mellitus (DM) is rising and substantially affecting the low-income countries, including Tanzania. Integrated management of TB and DM is becoming of importance in TB high burden countries. In this study, we sought to assess the availability and readiness of diabetes facilities to manage TB in Tanzania. Methods The present study was based on a secondary analysis of the 2014–2015 Tanzania Service Provision Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The aim of this research was to explore the barriers and facilitators to bidirectional screening in healthcare facilities in the Northern Region of Ghana. This study found that implementing bidirectional screening in public health facilities was achievable, when properly implemented, which is consistent with the findings of similar studies [6,22,23]. An increase in staff capacity and institutionalization of bidirectional screening were found to be enablers to the screening process, while delays in screening, fear and stigmatization of TB, poor collaboration between TB and DM units, and skewed funding for screening, were all found to hinder the successful implementation of bidirectional screening in the healthcare facility setting in the Northern Region of Ghana.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The aim of this research was to explore the barriers and facilitators to bidirectional screening in healthcare facilities in the Northern Region of Ghana. This study found that implementing bidirectional screening in public health facilities was achievable, when properly implemented, which is consistent with the findings of similar studies [6,22,23]. An increase in staff capacity and institutionalization of bidirectional screening were found to be enablers to the screening process, while delays in screening, fear and stigmatization of TB, poor collaboration between TB and DM units, and skewed funding for screening, were all found to hinder the successful implementation of bidirectional screening in the healthcare facility setting in the Northern Region of Ghana.…”
Section: Discussionsupporting
confidence: 92%
“…In 2013, the worldwide TB-DM comorbidity was over 1 million cases, reflecting 15% of the global tuberculosis burden [ 4 , 5 ]. Studies conducted in various countries from 2011–2013 found DM prevalence in TB patients to be from 25%-44% between 2011–2012 in three regions of India, 36% in Mexico, 17% in Tanzania and 40–45% in the South Pacific [ 5 , 6 ]. Projections indicate that by 2045, 629 million people will be living with DM, and the greatest share will be borne by LMICs [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical audit programme is built-in to increase accountability but also as a one of the learning system components. 11 The goal is to guide local decision but will also be communicated to the ministries responsible for Health and Regional Administration and Local Government Authorities.…”
Section: Methods and Analysis For Adept Modelmentioning
confidence: 99%
“…The tuberculosis facility that scores at least half (equivalent to the median value of 12.5% and above) in each domain and adding up to the overall of 50% or more were considered to have "high readiness" for the management of TB while those with less than 50% were considered to have "low readiness." The cut-off point used in this study was also used in the previous studies to dichotomize the outcome variable [25,[29][30][31][32][33].…”
Section: Plos Onementioning
confidence: 99%
“…Similarly, the Tanzania National Standard Treatment Guidelines has no information regarding screening for TB among DM patients [ 24 ]. Although one study found that DM health facilities had a low readiness to manage TB [ 25 ] there is a paucity of information about the capacity of tuberculosis facilities to manage diabetes mellitus. Knowing both scenarios can help to decide either to co-manage TB/DM in tuberculosis facilities or diabetes facilities.…”
Section: Introductionmentioning
confidence: 99%